PROFESSIONALISM AND MORAL INTENSITY OF AUDITORS ON WHISTLEBLOWING INTENSION ON MAKASSAR PUBLIC ACCOUNTANT OFFICE - Sri Wahyuni Nur; Nur Asia Hamid (Salewangang Institut Publishing, 2018)
This study aims to determine how auditor professionalism and the auditor's moral intensity and its influence on the intention to conduct whistle blowing in the Public Accounting Firm in Makassar. The focus of research is on the behavior of professionalism and morals of auditors in examining financial statements and expressing opinions about fairness in all material matters, financial position, results of operations, changes in equity and cash flows in accordance with accounting principles. Type of research is quantitative descriptive. Data used in this study is primary data in the form of questionnaires distributed to 10 Auditors as respondents. Questionnaires are used to measure the level of professionalism and moral intensity of auditors tested for validity and reliability. The analytical method used is multiple regression analysis using SPSS. The results showed that questionnaires distributed to 10 respondents were valid and reliable. The results of multiple regression analysis tests show that the level of professionalism and the moral intensity of auditors affect the intention to conduct whistleblowing where the higher the professionalism and moral intensity of an auditor, the higher the intention to conduct whistleblowing.